Narrative Continuation as Hypertextual Transformation of Receipt Parinaaz di Kafe Kroasia in Digital Humanities - Inrianto, Arsana Rendy; Aprilliana, Nasywa Lintang; Febriyanti, Ani Fadillah; Azzahrah, Najwa Alifia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This article examines narrative continuation as a form of hypertextual transformation of the short story Receipt Parinaaz di Kafe Kroasia within the framework of Digital Humanities. The study aims to transform the short story into a continuation narrative that extends the story beyond its ending, particularly at the final plot. In this study, narrative continuation is conceptualized not merely as an extension of the story, but as a transformation from hypotext to hypertext that reconstructs narrative meaning. This research employs a qualitative approach with narrative analysis used in the concept of hypertextuality by Gérard Genette and the theory of possible worlds by Marie-Laure Ryan. The analytical stages include identifying the intrinsic elements of the short story, determining the continuation node, and reconstructing the narrative into a new continuation form. The findings show that the resulting continuation narrative preserves the psychological dimensions of the main character while transforming the plot structure and expanding the narrative world, thereby generating new meanings related to trauma and identity. The transformation is materialized in the form of a continuation script and a digital storyboard presented as a flyer, demonstrating a practice of digital literary production within Digital Humanities. Also, this study proposes narrative continuation as a model for the digital transformation of Indonesian literary texts from print into digital forms.